TATA KELOLA MEDIA DIGITAL DALAM PEMBELAJARAN IPA SD: ANALISIS PELUANG DAN TANTANGAN ADMINISTRASI PENDIDIKAN - Akhmad Suyatno; Romi Kurniawan; Dita Afianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital media offers transformative potential for elementary science learning, but its implementation is severely hindered by immature educational administration governance. This study aims to comprehensively analyze the opportunities and challenges of digital media governance in elementary science from an educational administration perspective. A Systematic Literature Review adapted from the PRISMA protocol was conducted. Data were collected from Scopus, Web of Science, ERIC, and Sinta (2019-2024), yielding 27 eligible articles for thematic analysis based on educational administration functions. The findings reveal a paradox: while digital media significantly enhances abstract concept visualization and administrative efficiency, its sustainability is obstructed by a second-level digital divide. Major challenges include misaligned budget planning for maintenance, ambiguous digital asset organization, low teacher competence, and critical blind spots in student data privacy. The study concludes that shifting from mere infrastructure procurement to comprehensive digital lifecycle management is imperative for sustainable science education.